Space Utilization Change from Residential Into Commercial in Mojosongo, Surakarta - Nadya Astin Saraswati; Ragil Haryanto; Amin Pujiati; Mada Sophianingrum (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
The area of Mojosongo is a Perumnas which rapidly growing new growth center in Surakarta City. Existing commercial activities have expanded to enter the residential area. The emergence of this commercial area to facilitate trade activities and services between communities requires (demand) and people who sell services (supply) that can absorb labor in urban areas so that they can contribute to the Gross Regional Domestic Product (GRDP). The purpose of this study is to find out space utilization changes from residential into commercial fin Mojosongo in 2004-2019 and to know what factors influence it. The method used in this study is a quantitative and and the analytical techniques used are descriptive analysis techniques, spatial analysis and factor analysis. The subjects of this study is small-medium enterprises in the area of Mojosongo. The results of this study are 69% space utilization change from residential into commercial area in Mojosongo which is influenced by 4 factors: economic factors, the existence of housing, location, and accessibility.